Phenomena of limit-cycle oscillations in the Globus-M spherical tokamak. (3rd October 2018) - Yashin, A.Yu.; Bulanin, V.V.; Gusev, V.K.; Kurskiev, G.S.; Patrov, M.I.; Petrov, A.V.; Petrov, Yu.V.; Tolstyakov, S.Yu.
Abstract: The results of limit cycle oscillation (LCO) studies in the spherical Globus-M tokamak are presented. The oscillations of E   ×   B drift velocity, turbulence level, D α light emission, plasma density and magnetic field with the LCO frequency were simultaneously observed. Properties of two LCO regimes, with and without the transition to the H-mode, are compared. The results of a correlation analysis between the flows and turbulence require the use of a 1D model of the LCO development. The bicoherent analysis demonstrates that zonal flows dominate in LCOs. An up–down asymmetry of the poloidal magnetic field oscillations with the LCO frequency is found.